2015
DOI: 10.1504/ijnvo.2015.073848
|View full text |Cite
|
Sign up to set email alerts
|

Managing barriers of virtual communication in global new product development projects

Abstract: In virtual operating environments for new product development (NPD) increase the need to manage communication efficiently. The goal of communication is to reach a shared understanding; however, this is often challenging due to barriers that harm the communication process. Communication barriers typically cause misunderstandings and conflicts and hinder access to relevant information, causing delays in projects and some even fail in reaching their strategic or operational objectives. In addition to identifying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Communication is considered the “process of exchange of information between sender and receiver to equalize the information on both sides” (den Otter and Prins, 2002). In a communication process, a group or person transmits information to another group or person in order to establish a shared understanding of the topic (Lohikoski et al. , 2015; Morreale et al.…”
Section: Literature Review and Theoretical Modelmentioning
confidence: 99%
“…Communication is considered the “process of exchange of information between sender and receiver to equalize the information on both sides” (den Otter and Prins, 2002). In a communication process, a group or person transmits information to another group or person in order to establish a shared understanding of the topic (Lohikoski et al. , 2015; Morreale et al.…”
Section: Literature Review and Theoretical Modelmentioning
confidence: 99%
“…Another relevant issue in which the EC plays an important role in the relationship between ITC and IP deals with interorganizational coordination and collaborative work such as the one carried out in virtual innovation teams. In this sense, the main problem is communication barriers that cause misunderstandings, conflicts and consequently, delays in innovation projects (Gilson et al, 2014;Lohikoski et al, 2015). Barriers arise because when comparing virtual and face-to-face communication, the former involves a greater degree of difficulty in grasping the emotional state of the people with whom one is interacting causing biases and distortions (Ayoko et al, 2012); for example, people perceive an unfounded negative tone in emails that deal with work issues (Byron, 2008).…”
Section: Mediating Effects Of the Organization's Emotional Capabilitymentioning
confidence: 99%
“…There is also evidence that e.g. with prior positive experiences, team building and good communication skills, virtual work can be conducted efficiently (Harwick, 2013;Lohikoski & Haapasalo, 2013;Lohikoski et al, 2014). Certain teams had learnt to use wikis, blogs, instant messaging and web conferencing in such a way that oral communication was unnecessary (Reed & Knight, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In research there are controversial results in trust, which requires further studies in order to achieve theoretically grounded understanding (Martins et al, 2004;Seppänen, 2014). It has been previously claimed that virtual teams cannot transmit rich information; however, recent studies have shown that virtual communication can be rich if promoted by high level of trust or strong ties among team members (Harwick et al, 2013;Lohikoski et al, 2014). Hence, understanding trust in different contexts is important not only theoretically, but also in practice (Jarvenpaa et al, 2004).…”
Section: Introductionmentioning
confidence: 99%